THE BASIS OF STRATEGIC MANAGEMENT OF THE INNOVATIVE DEVELOPMENT OF THE SERVICE FIELD ASPECTS - Tukhliyev Bakhtiyot Makhmaziyaevich (American Journals, 2024)
The article deals with approaches to innovative development strategic management of the service sector at the state level. It also considers the innovation activity features in organizations of various sectoral subsystems services.
Keywords: Innovation, innovation process, innovative design, innovative project, innovative development, service organizations, innovation strategic management.